Keeping an eye on pink eye: a global conjunctivitis outbreak expert survey. Issue 5 (19th August 2021) - Kaur, Gurbani; Seitzman, Gerami D; Lietman, Thomas M; McLeod, Stephen D; Porco, Travis C; Doan, Thuy; Deiner, Michael S
Abstract: Background: Recurrent conjunctivitis epidemics are prevalent worldwide. Aetiologies are often undetermined. Methods: We surveyed conjunctivitis researchers about perceived trends in prevalence, incidence and aetiologies of conjunctivitis epidemics. Results: Of the 155 participants, 7% endorsed globally variable and dynamic microbial aetiologies of conjunctivitis epidemics. Increased incidence of conjunctivitis epidemics over the last decade were reported by 21% of respondents. Peak seasons differed between the northern and southern hemispheres. Conclusions: There is regional equipoise regarding the increasing incidence and emerging underlying aetiologies of epidemic conjunctivitis. Further investigation of global surveillance and microbial characterization of conjunctivitis outbreaks could improve prevention and outcomes.